Avaliação das propriedades mecânicas de um laminado de fibras de carbono e resina epóxi com diferentes parâmetros de cura - Fonseca, Mariana Hellen de Freitas (Universidade Federal Rural do Semi-Árido, 2017)
The intensive research about the parameters involved in composites materials is growing every day for the use of these in areas such as automotive, military and aeronautics. The use of composites materials is rightly gives according to get desirable properties combine with the joining of metals, ceramics and/or polymers. The carbon fiber has the flexibility to be processed in different ways and dependent on these may have excellent properties. Thus, it is now considered one of the main reinforcements in composite materials. If combined with epoxy resin, it is very attractive in applications that have properties on a fundamental point. Therefore, the objective of this work was to evaluate the various conditions of improvement of the manufacturing process and curing the carbon fiber and epoxy resin checking if differences are significant with changes in volume fraction of resin and curing process. For this, the curing will occurred due to the action of the vacuum, with the aid of the hydraulic press at a pressure of 1 tnf and without any pressure, all for the 5 hours. For each type of curing process was varied the volumetric fraction of the resin in 15%, 25%, 35% e 45%. Then, mechanical tensile, flexural and DMA was carried out and their results was evaluated to obtain the best relatives properties of the composite under analysis.
Monografia
Keywords: Materiais compósitos; Fibra de carbono; Ensaios mecânicos; Propriedades relativas; Composites materials; Carbon fiber; Mechanical tests; Relatives properties; ENGENHARIAS::ENGENHARIA MECANICA